2013
DOI: 10.1074/jbc.m113.458323
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 3 Regulates Cyclin A Stability

Abstract: Background: Cyclin A is a regulatory subunit of cyclin-dependent kinases that are key enzymes in the regulation of cell cycle progression. Results: Histone deacetylase 3 (HDAC3) regulates cyclin A deacetylation. Conclusion: HDAC3 regulates cyclin A stability by modulating cyclin A acetylation. Significance: HDAC3 regulates cell cycle progression by controlling cyclin A levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
(54 reference statements)
1
25
2
Order By: Relevance
“…In yeast, CDK1 can be acetylated at lysine 33, which is essential for proper growth (32). Moreover, a recent study using HeLa cells showed that HDAC3 deacetylates and prevents the ubiquitination of cyclin A (14). However, in our study, although we detected acetylated CDK1 in HCN cells, we did not observe any differences in CDK1 acetylation levels after HDAC3 inhibition or overexpression, possibly due to regulation by other HDACs.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…In yeast, CDK1 can be acetylated at lysine 33, which is essential for proper growth (32). Moreover, a recent study using HeLa cells showed that HDAC3 deacetylates and prevents the ubiquitination of cyclin A (14). However, in our study, although we detected acetylated CDK1 in HCN cells, we did not observe any differences in CDK1 acetylation levels after HDAC3 inhibition or overexpression, possibly due to regulation by other HDACs.…”
Section: Discussioncontrasting
confidence: 56%
“…The discrepancies in cell cycle defects after loss of HDAC3 may reflect alterations in the level of HDAC3 at different stages of the cell cycle. For instance, in HeLa cells, the levels of HDAC3 are reduced in metaphase due to proteasome degradation (14). However, in NSPCs, we observed consistently high levels of HDAC3 throughout the cell cycle (Fig.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…An abrupt loss of HDAC3 at metaphase facilitates cyclin A acetylation by PCAF/GCN5, which target cyclin A for degradation. Because cyclin A is crucial for S-phase progression and entry into mitosis, HDAC3 knockdown causes cell accumulation in the S and G 2 /M phases (20).…”
mentioning
confidence: 99%